Why do I study? The mediating effect of motivation and self-regulation on student performance - Ariani, Dorothea Wahyu (Business, Management and Economics Engineering, 2016)
The present study is designed to improve understanding of personal and situational effects on academic performance. This study examines relationship between flexible assessment system and academic performance mediated by self-regulation and academic motivation. This study also investigates moderated gender as a variable on the relationship models. A sample of 326 students of economics and business program were participated in the current study. The results indicate that academic motivational construct is a strong predictor of students’ self-regulation in learning and academic performance. Self-regulation mediates relationship between students’ academic motivation and students’ academic performance. Academic motivation and self-regulation also mediate the relationship between flexible assessment system and self regulation. The results also indicate that flexible assessment system does not have a direct relation with performance. These results are discussed with regard to the relevance of flexible assessment system, academic motivation, and self-regulation in increasing academic performance.